Godland - Palmason, Hlynur; Palmason, Hlynur; Hausswolff, Maria von; Sigurðsson, Ingvar Eggert; Crosset Hove, Elliott; Sonne, Vic Carmen (Curzon Film, 2023)
The struggle between the strictures of religion and our own brute animal nature plays out amid the beautifully forbidding landscapes of remote Iceland in this stunning psychological epic from director Hlynur Pálmason. In the late nineteenth century, Danish priest Lucas (Elliott Crosset Hove) makes the perilous trek to Iceland's southeastern coast with the intention of establishing a church. There, the arrogant man of God finds his resolve tested as he confronts the harsh terrain, temptations of the flesh, and the reality of being an intruder in an unforgiving land. What unfolds is a transfixing journey into the heart of colonial darkness attuned to both the majesty and terrifying power of the natural world. [www.janusfilms.com]
Keywords: Blu-Ray-Disc